Selected Stability Problems of Thin-Walled Columns and Beams - Szymczak, C.; Kujawa, M.
The article reviews a number of papers in the light of buckling analysis of thin-walled columns and beams. Stability of thin-walled columns and beams are considered a vital engineering science issue in both historical and present-day approaches. The paper refers to the recent authors' works of the 2012-2019 period, published in leading journals. Similar review of stability problems of thin-walled structures developed at Gdansk University of Technology is published in Szymczak (A review of stability problems of thin-walled structures developed at Gdansk University of Technology, 69-78, 2003, [58]), Szymczak (Selected problems of stability of thin-walled columns with bisymmetric cross-section, 111-128, 2012, [59]). This paper is a continuation of the earlier reviews. Only selected references are given.
Keywords: THIN-WALLED STRUCTURES